Surface-mediated priming during in vitro generation of monocyte-derived dendritic cells - Sauter, Alexander; McDuffie, Yvonne; Böhm, Heike; Martinez, A.; Spatz, Joachim P.; Otto, Silke (Scandinavian journal of immunology, 2015)
Ex vivo-generated human dendritic cells (DC) are most commonly generated from monocytes using standard cell culture dishes. To elucidate the effect of the plastic surface during the differentiation process, we compared a standard adhesive plastic dish with four different mainly non-adherent surfaces. Untouched monocytes were cultured for 3 days in the presence of IL-4 and GM-CSF. Time-lapse videos were recorded, and the phenotype of the cells was analysed by flow cytometry. The cytokine profiles were analysed using a 25-plex cytokine assay. The use of non-adherent surfaces led to a significant reduction in expression of CD14 and CD38, and a significant increase in expression of CD86 compared to standard culture dishes. Expression levels of DC-SIGN and PD-L2 were reduced significantly on cells cultured on non-adherent surfaces. The cytokine production was independent on the surface used. The surface-mediated priming should therefore be considered when aiming to induce specific immune responses. This is especially important with regard to DC-based immunotherapy, where an adjustment of the surface during the DC generation process might have highly beneficial effects.
First published 07 November 2014
Gesehen am 16.06.2020